1998
DOI: 10.1097/00005768-199808000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Coagulation and thrombomodulin in response to exercise of different type and duration

Abstract: The data demonstrated that prolonged exercise is necessary for exercise-induced activation of coagulation resulting in thrombin and fibrin formation and suggested that endothelial cell activation possibly due to mechanical factors associated with running might play a role.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
42
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 23 publications
6
42
0
Order By: Relevance
“…In general, exercise has been shown to result in a transient, but balanced, activation of coagulation and fibrinolytic cascades [Herren et al, 1992]. TAT and PTF1,2 are increased after long duration of high-intensity (over 70% of VO 2 max) aerobic exercise, but not after highintensity resistance exercise [Weiss et al, 1998]. Further, exercise duration of BFR exercise protocol is about 6 min including rest period between sets.…”
Section: Discussionmentioning
confidence: 99%
“…In general, exercise has been shown to result in a transient, but balanced, activation of coagulation and fibrinolytic cascades [Herren et al, 1992]. TAT and PTF1,2 are increased after long duration of high-intensity (over 70% of VO 2 max) aerobic exercise, but not after highintensity resistance exercise [Weiss et al, 1998]. Further, exercise duration of BFR exercise protocol is about 6 min including rest period between sets.…”
Section: Discussionmentioning
confidence: 99%
“…Despite much interest in soluble TM as a marker for endothelial injury, no data are available which focused on the the effect of training on TM concentration. An acute and prolonged bout of exercise (running, but not swimming or cycling) has been shown to increase soluble TM concentrations [39]. However, the acute effect of intense exercise could differ from the adaptative response of endothelium to a regular exercise programme, as for other coagulation parameters.…”
Section: Discussionmentioning
confidence: 99%
“…It was also reported that in 11 healthy male subjects irrespective of the type of exercise they performed, alterations in markers of thrombin and fibrin formation were pronounced after 1 h exercise. In this study of high impact, it was suggested that prolonged exercise is necessary for exercise-induced activation of coagulation resulting in thrombin and fibrin formation [16] . In 15 healthy individuals who performed strenuous exercise for 15, 45 and 90 s, it was observed that this exercise did not induce blood coagulation, whereas fibrinolysis, e.g., generation of tissue-plasminogen activator "t-PA" was increased after 15 s and remained high through the duration of exercise.…”
Section: Introductionmentioning
confidence: 98%